Study of Mutagenic Effect of Coccinea cordifolia (Linn.) Cogn. Leaf Extract on Neurospora crassa Fungus - Bhuiyan, M Nazrul Islam; Mozmader, TIMA; Hoque, M Amirul; Akter, Sumi; Islam, M Rafiqual (Bangladesh Journal of Scientific and Industrial Research, 2009)
Coccinea cordifolia (Linn.) Cogn. leaf extract showed significant mutagenic effect on Neurospora crassa fungus. Observation after 24 hours, control showed 2.9 cm linear vegetative growth of the mycelia where C. cordifolia leaf with N. crassa showed 0.25 cm growth and it is 12 times less than the control. Besides, 0.5, 1.0, 1.5, 2.0, 3.0 and 4.0 ml extract showed gradual decrease of growth of mycelia. This result indicates that this plant was suitable for induction of mutation in N. crassa. After mutation of N. crassa Ema (5297) conidia with C. cordifolia leaf extract, 6 types of mutants were found namely- dirty, ropy, albino, mat, cauliflower, conidial brand. Albino mutant showed highest frequency (35%) where ropy showed lowest frequency (5%). Key words: Neurospora crassa, Coccinea cordifolia, Mutants, Dirty, Ropy, Albino, Mat,Cauliflower and Conidial brand. DOI: 10.3329/bjsir.v44i2.3675 Bangladesh J. Sci. Ind. Res. 44(2), 215-220, 2009